THE VALIDITY OF MAGNETIC RESONANCE IMAGING IN DETERMINING PREOPERATIVE NODAL STAGING IN RECTAL CANCER - Ana Lazarova; Ljuben Arsenkov; Stefan Arsenkov (Македонско лекарско друштво = Macedonian Medical Association, 2020)
Abstract Introduction. The basic diagnostic tool in preoperati-ve staging of rectal cancer is magnetic resonance ima-ging (MRI), which allows the selection of patients who in addition to surgical treatment, are candidates for preoperative chemoradiotherapy (neoadjuvant treatment). The aim of this study was to demonstrate the validity of magnetic resonance imaging in determining the nodal stage (stage N) of rectal cancer preoperatively. Methods. In this study 82 patients with colonoscopy proven rectal cancer, aged 43 to 87 years (an average age of 66.65), were treated. Magnetic resonance imaging (MRI) was performed pre-operatively and the N stage of the disease was deter-mined. The MRI was made with a 1.5T magnet in stan-dard pulse sequences SAG T2, AX T1, AX T2, AX DWI. Results. The results obtained for the N stage with mag-netic resonance imaging were correlated with the pa-thohistology finding postoperatively taken as the gold standard in determining the sensitivity and specificity of magnetic resonance imaging. The sensitivity and specificity of MRI in determining the N0 stage of rectal carcinoma was 36.6% and 48.8%, respectively. The sensitivity and specificity of MR in determining the N1 stage of rectal carcinoma was 35% and 79%, respectively. The sensitivity and specificity of MR in determining the N2 stage of rectal carcinomas were 25% and 98.6%, respectively. Conclusion. Magnetic resonance imaging is the basic and also most important diagnostic modality in preopera-tive staging of rectal cancer and provides a clear in-sight into nodal status, with an accuracy of 43% to 85%.
ВАЛИДНОСТА НА МАГНЕТНАТА РЕЗОНАНЦА ВО ОДРЕДУВАЊЕ НА ПРЕДОПЕРАТИВНИОТ НОДАЛEН СТЕЈЏИНГ КАЈ РЕКТАЛЕН КАРЦИНОМ
Keywords: MRI; rectal cancer; preoperative N staging